Abiotic stress and induced DNA hypomethylation cause interphase chromatin structural changes in rice rDNA loci - Santos, Ana Paula (2012)
Global climate change, i.e. higher and more variable temperatures, and a gain in soil salinity are increasing plant stress with direct consequences on crop yield and quality levels. Rice productivity is strongly affected by abiotic stress conditions. The regulation of chromatin structure in response to environmental stress is poorly understood. We investigated the interphase chromatin organization from rice plants in non-stress versus stress conditions. We have used a cytogenetic approach, based on fluorescence in situ hybridization (FISH) with 45S, 5S rDNA and centromeric probes on rice tissue sections. The abiotic stress conditions included cold, heat and mild salinity and were applied during seed germination. In contrast to cold, saline and heat stresses caused extensive decondensation of 45S rDNA chromatin and also an increase in the distance between the 2 homologous 5S rDNA loci. 5-Azacytidine (5-AC), a DNA hypomethylating drug, greatly increased 45S rDNA chromatin decondensation and interestingly was able to induce polarization of centromeres in rice interphase nuclei. The abiotic stresses tested did not perturb the spatial position of centromeres, typically with circular arrangement around the nucleolus. The results suggest a role for chromatin plasticity in a world of climate changes.